SISTEM INFORMASI DIGITALISASI PENGENALAN RUMAH ADAT SUMATERA SELATAN DI DEKRANASDA PALEMBANG - Fenny Purwani; Dzurriya Alkarimah; Irmalia Irmalia; Rizki Triwahyudi (Jurnal Riset Sistem Informasi, 2026)
This project aims to develop the Information System for the Digitalization of South Sumatra Traditional Houses at Dekranasda Palembang as an educational and cultural preservation platform based on modern technology. The research is motivated by the limited use of conventional information media in the traditional house complex, which restricts visitors from obtaining an interactive and comprehensive learning experience. The study applies a Software Development Life Cycle (SDLC) approach with a prototyping model, consisting of the stages of requirements analysis, system design, development, testing, and evaluation. Data were collected through field observations, interviews with Dekranasda officers, literature review, and cultural documentation. The results show that the developed web-based information system effectively presents data on traditional houses from 17 regencies and cities across South Sumatra through interactive features such as a cultural gallery, digital map, QR Code integration, and 360° Virtual Tour. The system has proven effective in enhancing cultural education, improving information accessibility, and supporting digital transformation in the regional tourism and cultural sectors. Thus, this system serves not only as a technological innovation but also as a strategic medium for the sustainable preservation of South Sumatra’s cultural heritage